Edukasi Sampah Plastik dan Pengolahannya Menjadi Barang Hias - Bahri, Saeful; Faris, Nahrul; Nasruhi, Moch.; Masitoh, Rikha; Amalia, Rizka; Kholifah, Siti (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2023)
One of the problems that cannot be solved in Indonesia is the way waste is processed, for example the problem in Gembong Kulon Village. This is because the final disposal site (TPA) is quite far from residential areas. The aim of holding this waste education is to provide knowledge about how to process and utilize inorganic waste (plastic) into goods of selling value. The research method used is a persuasive lecture or education approach and direct practice on how to collect and sort waste, both organic and inorganic. The output results obtained from this work program regarding environmental education and plastic waste are an increase in students' understanding of waste and how to process it as well as fostering creativity in these students.